Analisis Manajemen Risiko Operasional Pada Toko Grosir TRI JAYA Untuk Meningkatkan Keberlanjutan Usaha - Refansa Febriana Akbar (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyze operational risk management at Trijaya Wholesale Store in an effort to maintain business sustainability. Located in Ciheras Village, the store faces various operational challenges, such as supply delays, shortages of fast-moving goods, increases in fuel costs, price fluctuations, and the lack of a digital marketing strategy. The research uses a qualitative descriptive method through interviews, observations, and documentation to obtain a comprehensive picture of these risks. The results show that some risks have a high probability and impact and therefore need to be addressed as a priority. These risks directly affect the smooth distribution, operational efficiency, and competitiveness of the store. To mitigate the impact of these risks, the store is advised to implement a minimum stock system, improve coordination with suppliers, perform regular vehicle maintenance, improve financial record-keeping, and begin utilizing social media for promotion. With better risk management, Toko Grosir Trijaya is expected to retain customers and improve the sustainability of its business amid market competition.